Rheological properties of rice-locust bean gum gels from different rice varieties - Correa, María Jimena (2013)
Pasting and gelatinization behavior of rice gels from Japonica (Ariete, Euro), Indica (Gladio, Suriname) and waxy (Glutinous) varieties were analyzed. These varieties differ widely in amylose contents and differential scanning calorimetry (DSC) gelatinization temperatures. Besides, the effect of locust bean gum (LBG) addition and the impact of successive viscoanalyser multiple-heating-cooling and freezing-thawing cycles on the gels pasting viscosities (peak-ηpeak, trough-ηmin, final-ηfinal), viscoelasticity by oscillatory rheometry and syneresis were evaluated.Flours from different rice varieties exhibited distinct viscoanalyser curves and viscoelastic behaviors as well as different degree of syneresis. Euro and Ariete showed lower setback from peak (ηfinal-ηpeak) and syneresis, whereas Waxy had ηpeak superior to ηfinal (negative setback) and did not exhibit syneresis.The addition of LBG (0.5%, 1%, 2% w/w) significantly modified the pasting viscosities in single and multiple profiles, viscoelastic and syneresis properties of rice gels and the extent of the effect was dependent of rice varieties. In general, the addition of LBG caused an increase in peak, final and minimum viscosities but only rice gel from Ariete variety exhibited reduction of setback. Reduction of syneresis seems evident for 0.5% LBG addition on rice gels from Suriname and Ariete varieties, but 1% was needed for Gladio variety.Successive multiple-heating-cooling cycles led to a progressive decrease on viscosity after a second cycle for Japonica and Waxy varieties, in Indica varieties these peak viscosities were maintained or decreased in a lesser degree, syneresis was higher than in single cycles and is largely reduced in the presence of LBG.This study provides knowledge of different rheological behavior of rice varieties that would be relevant for utilization of rice gels on food applications.